2021
DOI: 10.3390/cells10102536
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Radiation Desiccation Response Regulon of the Radioresistant Bacterium Deinococcus radiodurans by Integrative Genomic Analyses

Abstract: Numerous genes are overexpressed in the radioresistant bacterium Deinococcus radiodurans after exposure to radiation or prolonged desiccation. It was shown that the DdrO and IrrE proteins play a major role in regulating the expression of approximately twenty genes. The transcriptional repressor DdrO blocks the expression of these genes under normal growth conditions. After exposure to genotoxic agents, the IrrE metalloprotease cleaves DdrO and relieves gene repression. At present, many questions remain, such a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…The PprI/DdrO-mediated regulatory system has been recognized as a unique transcriptional inhibition and removal system of D. radiodurans in response to DNA damage. Under environmental stress conditions, PprI, a metal-dependent protease, is activated to specifically cleave the C-terminal region of the DdrO, abolishing its DNA binding activity, and resulting in the expression of DNA damage repair genes that are inhibited by the DdrO (48). Enrichment analysis of the downregulated genes in the mutant reveal their involvement in vital cellular processes closely related to respiration, translation, RNA metabolism, and electron transfer ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The PprI/DdrO-mediated regulatory system has been recognized as a unique transcriptional inhibition and removal system of D. radiodurans in response to DNA damage. Under environmental stress conditions, PprI, a metal-dependent protease, is activated to specifically cleave the C-terminal region of the DdrO, abolishing its DNA binding activity, and resulting in the expression of DNA damage repair genes that are inhibited by the DdrO (48). Enrichment analysis of the downregulated genes in the mutant reveal their involvement in vital cellular processes closely related to respiration, translation, RNA metabolism, and electron transfer ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this scenario, UvrC is more likely to be recruited as a binary complex with UvrB to sites of DNA damage. In D. radiodurans , although the uvrC gene is not part of the conserved radiation/desiccation response (RDR) regulon ( 83 , 84 ), its expression has been reported to be upregulated in response to ionizing radiation, but to a lesser extent than the uvrA , uvrB and uvrD genes ( 85 ), suggesting that the relative abundance of the UvrABC machinery during the response to DNA damage may be different to that observed in E. coli and some UvrC may remain unbound. In this case, UvrC may be recruited directly to UvrB-DNA pre-incision complexes aided by its relatively strong binding affinity for damaged DNA.…”
Section: Discussionmentioning
confidence: 99%
“…IrrE is a metalloprotease that cleaves the dimeric form of DdrO bound to the RDRM motif of the RDR regulon. By inactivating the repressor DdrO, gene expression mediated by the RDR regulon is activated [75,78]. We expect this is an example of a defined redox-sensing pathway.…”
Section: Redox-switched Regulators and Redox Signallingmentioning
confidence: 97%
“…Very recently, chromatin immunoprecipitation sequencing (ChIP-Seq) analysis and RNA sequencing (RNA-Seq) analysis showed that the radiation/desiccation response (RDR) regulon operated through the cis-acting sequence RDRM (Radiation Desiccation Response Motif), the trans-acting repressor DdrO and the protease IrrE possibly controlled a unique IS family [75]. The authors performed a systematic and comprehensive sequence analysis for the RDR motif and newly found the DdrO target genes, which involved two Tpase that included the IS5 and Tn3 families.…”
Section: Redox-switched Regulators and Redox Signallingmentioning
confidence: 99%